Tumor necrosis factor-alpha modulates effects of aryl hydrocarbon receptor ligands on cell proliferation and expression of cytochrome P450 enzymes in rat liver "stem-like" cells - Umannová, Lenka; Procházková, Jiřina; Machala, Miroslav; Krčmář, Pavel; Májková, Zuzana; Hennig, Bernhard; Kozubík, Alois; Vondráček, Jan (Toxicological sciences, 2007)
Various liver diseases lead to an extensive inflammatory response and release of a number of proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-alpha). This cytokine is known to play a major role in liver regeneration as well as in carcinogenesis. We investigated possible interactions of TNF-alpha with ligands of the aryl hydrocarbon receptor (AhR) and known liver carcinogens, such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and coplanar 3,3',4,4',5-pentachlorobiphenyl (PCB 126). These compounds have been previously found to disrupt cell cycle control in contact-inhibited rat liver WB-F344 cells, an in vitro model of adult liver progenitor cells. TNF-alpha itself had no significant effect on the proliferation/apoptosis ratio in the WB-F344 cell line. However, it significantly potentiated proliferative effects of low picomolar range doses of both TCDD and PCB 126, leading to an increase in cell numbers, as well as an increased percentage of cells entering the S-phase of the cell cycle. The combination of TNF-alpha with low concentrations of AhR ligands increased both messenger RNA (mRNA) and protein levels of cyclin A, a principle cyclin involved in disruption of contact inhibition. TNF-alpha temporarily inhibited AhR-dependent induction of cytochrome P450 1A1 (CYP1A1). In contrast, TNF-alpha significantly enhanced induction of CYP1B1 at both mRNA and protein levels, by a mechanism, which was independent of nuclear factor-kappaB activation. These results suggest that TNF-alpha can significantly amplify effects of AhR ligands on deregulation of cell proliferation control, as well as on expression of CYP1B1, which is involved in metabolic activation of a number of mutagenic compounds.
Keywords: Liver; financování organizované; Animals; Gene Expression Regulation, Enzymologic; proliferace buněk; vztah mezi dávkou a účinkem léčiva; regulace genové exprese enzymů; Stem Cells; Polychlorinated Biphenyls; lékové interakce; játra; Drug Interactions; fixní kombinace léků; Tumor Necrosis Factor-alpha; polychlorované bifenyly; polychlorované dibenzodioxiny; Rats, Inbred F344; Epithelial Cells; kmenové buňky; Carcinogens; kultivované buňky; Cytochrome P-450 CYP1A1; Ligands; Financing, Organized; Cells, Cultured; Receptors, Aryl Hydrocarbon; TNF-alfa; Dose-Response Relationship, Drug; karcinogeny; Aryl Hydrocarbon Hydroxylases; cytochrom P-450 CYP1A1; potkani inbrední F344; Cell Proliferation; Polychlorinated Dibenzodioxins; krysa rodu Rattus; zvířata; epitelové buňky; Rats; Drug Combinations; aromatické hydroxylasy; ligandy